Morphological, lytic, and genetic characteristics of three Brucella phages isolated from Inner Mongolia Autonomous Region - Yu Zhang; Yu Zhang; Dongri Piao; Qingqing Xu; Yu Fan; Hongyan Zhao; Kun Li; Guozhong Tian; Kuo Han; Hai Jiang (Frontiers in Microbiology)
This study comprehensively examined three Brucella phages (A1, NMY-1, and NMY-2) isolated from Inner Mongolia Autonomous Region. Electron microscopy classified them as short-tailed phages. A1 and NMY-1 lysed smooth strains of Brucella abortus, Brucella melitensis, and Brucella suis, while NMY-2 lysed rough strains of Brucella melitensis and Brucella canis. The optimal multiplicity of infection for A1, NMY-1, and NMY-2 was lower than that of TbC. A1 and NMY-2 had short growth cycles, and NMY-1 had a long one. All three phages showed high stability against temperature, pH, and ultraviolet exposure. Their genomes were double-stranded DNA, about 38 kb long with a 48% GC content. For each phage, 53 genes were predicted, with no drug-resistance, virulence, or lysogenic genes identified. SNP and InDel analysis revealed significant differences in genes encoding hypothesized tail-collar proteins. Based on SNP data, the phylogenetic tree indicated that phage BkW (GenBank: KC556893) was the closest relative of A1, NMY-1, and NMY-2. These findings significantly enhance our understanding of Brucella phage diversity, which is crucial for developing phage-based biocontrol strategies. The host-lysis spectra can guide the selection of effective phages for treating Brucella infections. The absence of harmful genes makes these phages potential safe candidates for phage therapy. Moreover, the genetic and phylogenetic insights support further research on phage evolution and classification.